Impact of Workplace Violence Educational Program on SelfConfidence for Nursing Staff Working in Psychiatric Hospital (Indian Journal of Public Health Research & Development, 2020)
Inpatient mental health clinicians need to feel safe in the workplace. They require confidence in their ability to work with aggressive patients, allowing the provision of therapeutic care while protecting themselves and other patients from psychological and physical harm. The aim of this study is to evaluate the impact of educational training program on self- confidence for nursing staff working in psychiatric hospital. Design: A quasi-experimental design” pre-posttest assessment” was utilized for the current study. A sample of convenience of 45 psychiatric nurses who agree to participate and were in Al-Abbassia mental health hospital were included. Two tools were utilized in the current study including Socio- Demographic including Department Data Sheet, Confidence in Managing Service user Aggression. The results showed that: there was a highly statistically significant difference was found for all items in nurses’ pre versus post self- confidence assessment. Also there was a positive significant correlation between nurses’ level of self-confidence and the frequency of isolation for the patients & nurses’ years of experience in pre & post assessment, while there is no significance correlation between nurses’ level of self-confidence and their age, gender, or duration of patient’s isolation. To conclude that, nurses who received the educational training program about workplace violence showed higher score in their post assessment of self- confidence than before receiving the program. So the research hypotheses was accepted. Further studies was recommended in addressing the effect of training on staff behavior to be measured through direct observation.
Keywords: Workplace Violence, self?confidence, Psychiatric Nursing Staff.